(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Vitex altissima has been conventionally utilized for its wide-ranging properties in the management of oxidative stress and inflammation. The present investigation was centered on the quantification of the anti-inflammatory efficacy of Vitex altissima. The samples were evaluated for their ability to impede the activity of proteinase, denature proteins, and stabilize the membrane of human red blood cells (HRBC). The present study investigated the inhibitory impact of extracts on the production of total cyclooxygenase, lipoxygenase-5 (5-LOX), myeloperoxidase (MPO), and nitric oxide (NO) using the RAW 264.7 cell line. Furthermore, the antioxidant properties were assessed through the employment of both DPPH assay and reducing power assay. According to the findings, the methanolic extract of Vitex altissima (VAME) was identified as the most efficacious fraction with anti-inflammatory and antioxidant properties. The findings indicate that the extracts exhibited dose-dependent inhibition of proteinase, protein denaturation, and hemolysis of HRBC membrane, which is beneficial. The extracts of Vitex altissima, when treated at concentrations that are not cytotoxic, were observed to have a significant effect in reducing the activity of COX, 5-LOX, and MPO in RAW 264.7 cell line treated with LPS. This resulted in a decrease in NO levels. The dose-dependent increase in in vitro anti-inflammatory activity of Vitex altissima suggests its potential use as a pharmacological agent for the management of diseases related to inflammation. Additional comprehensive phytochemical investigations, in conjunction with in vitro and in vivo analyses, are necessary to identify the active constituent within the extract.